(untitled) (East West Medical College Journal, 2024)
Postdated pregnancy is not so uncommon in obstetric practice. When a pregnancy crosses the expected date of delivery (beyond 280 days) it is called postdated pregnancy. The incidence is about 7% of all pregnancies. This prospective observational study was carried out in 165 postdated pregnancies admitted in the Department of Obstetrics & Gynaecology, during a period of 3 years from January 2021 to December 2023 . Majority of the patients were below 25 years of age (47.88%) and primigravida (41.82%). Most of the patients belonged to rural areas (55.75%) and were middle socio-economic status group (45.45%). The majority of these postdated women were delivered by NVD (52.12%), followed by LSCS (32.72%) and instrumental (15.15%). Postdated pregnancy was associated with perinatal complications like meconium aspiration syndrome, oligohydramnios, fetal birth injuries, septicemia, shoulder dystocia, non-reassuring fetal heart rate status, fetal distress in labour. There was an increased risk of maternal complications like increased caesarean section rate, post-partum hemorrhage (PPH) ,cervical tear, perineal tear. Management of postdated pregnancy is challenging. Careful advice and timely interventions can reduce fetomaternal complications. EWMCJ Vol. 12, No. 1&2, January-July 2024: 94-98